THE FIRST REPORT ON THE ISOLATION OF ENTEROTOXIGENIC ESCHERICHIA COLI AS A CAUSE OF INFANTILE DIARRHEA IN IRAN - S.Mohadjer; A.Bidanjiri; R. Hafezi; A.H.Hamidi (Tehran University of Medical Sciences, 1982)
The role of enterotoxigenic E.coli as a causative agent in diarrheal disease was studied among 100 cases of infant and children 0-2 years of age. Routine bacteriological methods were used for identification enteropathogenic E.coli, Salmonella, Shigella and Vibrio cholera. The ability of E.coli strains to produce toxin was assayed in animal models (rebbit-ileal loop and suckling mice) and in tissue-culture (Y1-adrenal cell). A total of seven enterotoxin producing strains of E.coli were isolated. Three of these strains were producing both (heat-labile-LT) and heat-stable (ST) enterotoxin). The other four strains were producing only heat- stable enterotoxin which was lost during storage. The rate of isolation for other enteropathogenic bacteria such as Salmonella, Shigella and enteropathogenic E.coli was 7%, 4% and 13% respectively. No Vibrio cholera or yersinia enterocolitica was isolated from the age group under the study.